PENTINGNYA PENGELOLAAN KECERDASAN EMOSIONAL TERHADAP KINERJA SEORANG AUDITOR - Dea Endraning Oktaviani; Kartika Pradana Suryatimur (Bajang Institute, 2022)
As accountants play an increasingly important role in companies and institutions, many studies have been conducted to learn more about the factors that affect the performence of auditors. There are many factors that affect auditors performence. One of is emotional intelligence. Therefore, this study aims to analyze the importance of emotional intelligence management to auditor performence. The purpose of this study is the previousstudy on the impact of emotional intelligence on auditors performence. The research method utlizes literature review and descriptive research techniques, with an emphasis on systemativ interpretation of the fact obtained during the research. The result of this study is that EQ management is important to auditors performence. Emotional stable auditors will also give a good relut.